Microfluidic bioreactor for harvesting bio-electricity. - Arie Putra Suhendro. (2013)
Microbial fuel cell (MFC) utilizes microorganisms (bacteria) and substrate to generate electrical current. Nowadays, MFC in micro size or called microfluidic fuel cell have been receiving interest from researchers. Numerous studies have successfully assembled microfluidic fuel cell, but most of them used gold as electrodes which tend to have high fabrication costs. This project is conducted to design and fabricate a microfluidic bio-reactor for culturing bacteria and harvesting bioelectricity, especially using material that relatively inexpensive as electrode. Three studies have been done to achieve this objective, production 3D graphite-PDMS composite electrode, investigation of carbon paste and carbon tape as electrodes, and designing microfluidic fuel cell. In the first study, polyurethane mold was created from glass slide master and PDMS as mediator. The mold’s channel was then filled with graphite particles. After that, PDMS was poured onto the mold, cured, and peeled followed by conductivity test. Based on the result, the composite did not conduct any electricity and cannot further used as electrode. Carbon black nanoparticles may be tried out in the future as it was successfully used in other study. In the next study, conductivity test on different carbon paste and carbon tape samples were done and results showed that they have potential to be used as electrodes in microfluidic fuel cell. Therefore three microfluidic fuel cell designs were proposed focusing on carbon tape and carbon paste as electrodes. These designs can be assembled and tested in the future.